(untitled) (gjstudies, 2024)
This research investigates the critical gap between rapid technological advancementsin auditing practices and the comparatively slow adaptation of accounting educationcurricula. As auditing increasingly incorporates artificial intelligence, data analytics,blockchain verification, and continuous monitoring systems, traditional accounting education models rooted in manual procedures and periodic sampling face obsolescence.This paper presents a novel framework for accounting education transformation thatmoves beyond simply adding technology courses to existing programs. Instead, we propose a fundamental reimagining of accounting pedagogy through three interconnecteddimensions: cognitive integration of technological thinking within core accounting concepts, experiential learning through simulated audit environments that mirror contemporary digital workplaces, and ethical scaffolding that addresses the unique moralchallenges posed by algorithmic decision-making in financial verification. Our methodology employs a longitudinal design tracking accounting graduates from traditional andtransformed programs over their first three professional years, combined with Delphistudies involving audit partners, technology officers, and accounting educators. Thefindings reveal that graduates from transformed programs demonstrate significantlyhigher technological adaptability, problem-solving efficacy in data-rich environments,and ethical reasoning in technology-mediated audit scenarios. This research contributesoriginal insights by framing accounting education adaptation not as a curricular add-on1Published: 2024-11-10but as a paradigmatic shift in how future auditors are prepared to function as humantechnology hybrids in an increasingly automated verification landscape. The paperconcludes with a scalable implementation model for accounting programs seeking tobridge the technological adaptation divide while preserving the profession’s core valuesof integrity, skepticism, and public trust.